Positioning using GNSS and IMU - Zhang, Jingyang (Nanyang Technological University, 2021)
MEMS-based inertial guidance system (SINS) and global positioning system (GPS) combined navigation system has become a research and development hotspot in the field of global navigation system with a very broad application prospect due to its low cost, excellent navigation capability and strong complementarity be tween each other. The information fusion technology is one of the main directions in the research and application of SINS/GPS combined navigation system, and it is important to study how to improve the performance of MEMS/GPS combined navigation system in terms of accuracy, reliability and continuity. The details of this dissertation are as follows. First, the background of combined navigation system and the basic principles of inertial navigation system and INS/GPS combined navigation are introduced, and the linear and nonlinear error models of MEMS inertial guidance are derived. Secondly, the error characteristics of inertial sensors, including systematic and random errors, are analyzed; the random errors of MEMS gyroscopes and accelerometers are analyzed using the Allan variance method. Finally, the combined MEMS/GPS navigation system model is simulated and compared with the actual experimental data using the EKF for nonlinear systems.